2020
DOI: 10.1016/j.sdentj.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of the prevalence and severity of maxillofacial fractures resulting from motor vehicle accidents in Riyadh, Saudi Arabia

Abstract: Objectives To investigate the prevalence and severity of maxillofacial fractures resulting from motor vehicle accidents (MVAs) at King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia. Materials and methods A cross-sectional study of 325 males (89%) and 47 females (9%) was conducted that retrospectively reviewed records of patients referred to oral and maxillofacial surgery department from emergency department from 1st January 2016 to 31st December 2017 at KAMC, Riya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
5
14
0
Order By: Relevance
“…9,10,18-20 Such high prevalence was attributed to the fact that men are more empowered in society, involved in more outdoor activities, and more likely to be involved in reckless driving compared to female drivers. 10,20 Furthermore, our reported mean age of the involved patient was 29.9 years, which is very much similar to the findings of published studies concluding that this age group is associated with increased self-dependence, high activity, and social interactions that may increase their susceptibility to reckless driving and more road usage. 9,10,[17][18][19][20] Regarding the location of the injury, published data from Saudi Arabia reported that most maxillofacial injuries were in the lower face with no reported occurrence in the upper face during both study periods, before and after the implementation of the Saher law enforcement system.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…9,10,18-20 Such high prevalence was attributed to the fact that men are more empowered in society, involved in more outdoor activities, and more likely to be involved in reckless driving compared to female drivers. 10,20 Furthermore, our reported mean age of the involved patient was 29.9 years, which is very much similar to the findings of published studies concluding that this age group is associated with increased self-dependence, high activity, and social interactions that may increase their susceptibility to reckless driving and more road usage. 9,10,[17][18][19][20] Regarding the location of the injury, published data from Saudi Arabia reported that most maxillofacial injuries were in the lower face with no reported occurrence in the upper face during both study periods, before and after the implementation of the Saher law enforcement system.…”
Section: Discussionsupporting
confidence: 89%
“…10,20 Furthermore, our reported mean age of the involved patient was 29.9 years, which is very much similar to the findings of published studies concluding that this age group is associated with increased self-dependence, high activity, and social interactions that may increase their susceptibility to reckless driving and more road usage. 9,10,[17][18][19][20] Regarding the location of the injury, published data from Saudi Arabia reported that most maxillofacial injuries were in the lower face with no reported occurrence in the upper face during both study periods, before and after the implementation of the Saher law enforcement system. 10 Our findings are in contrast to the work of Alasseri et al in that before the implementation of TLERs, lower face and mid-face injuries have an equal occurrence of 38.2% each and after the TLERs adoption, most of the injuries were of mid-face accounting for 57.3% followed by lower face at 36.4%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Orbital fractures were observed as the fourth most common maxillofacial bone fractures with majority presenting as isolated orbital floor fractures. Similar findings have been reported in the literature [5,11,46]. Maxillofacial fractures can be treated with either closed reduction, ORIF or a combination of these methods.…”
Section: Discussionsupporting
confidence: 85%